Hermeutical Analysis on Ibn Arabi's Poems - Fauzan, Muhammad; Rusmana, Dadan; Sakinah, R. Myrna Nur (Jurusan Sastra Indonesia, 2023)
The purpose of this research was to analyze or interpret Ibn Arabi’s poems on Tarjuman Al-ashwaq. The method used in this research is a qualitative descriptive method with content analysis, by analyzing poems with a hermeneutic approach. This abstract explores the use of hermeneutical analysis in interpreting the poems of Ibn Arabi, a prominent Sufi philosopher and poet. Hermeneutical analysis is a method of interpretation that focuses on the meaning and significance of a text. The poems of Ibn Arabi’s poems have many symbolism and metaphors that are rooted in Islamic mysticism, and hermeneutical analysis provides a framework for understanding the deep spiritual and philosophical themes in his poems. Through this approach, the abstract examines the various layers of meaning in Ibn Arabi's poems, including the spiritual insights they offer, the relationship between the individual and the divine, and the concept of divine love. Overall, this abstract highlights the importance of hermeneutical analysis in unlocking the profound and complex meaning of Ibn Arabi's poems.